A Floating Homeland: (De)Constructing Canadianness from the Insider‑Outsider Perspective of Japanese‑Canadians - Madeja, Rafał (Romanica Silesiana)
On the basis of Joy Kogawa’s Obasan, the main objective of this paper is to take under the scrutinizing eye how the central protagonist retrieves a selective portion of her childhood memories during the Second World War in an effort to reshape her fragmented identity as a Japanese‑Canadian and to deal with the feeling of displacement. Analyzing essential memories, conversations, and stories within the plotline, the aim is to demonstrate that Naomi, in order to fight her identity crisis and feeling of displacement — due to the Japanese community’s sense of belonging in Canada being shuttered by the Canadian government — recasts her personal experiences to her own needs for the identity refashioning in‑between cultures, therefore, in Homi Bhabha’s terms, giving life to a sort of “Third Space.” This paper will therefore demonstrate numerous ways in terms of which the protagonist intrudes upon iconic wilderness and rural landscapes in Canada — hitherto emptied of the indigenous and minorities and thus functioning as a sort of privileged sites of national identity — so as to transform them into heterogeneous and more inclusive spaces, breaking the binary opposition between away and home, a newcomer and native. Significantly, the protagonist’s storytelling may be distinguished by great attention to nature, botanical imagery, and landscapes shaped by experiences of displacement, and it may be argued that the novel is targeted at re‑visiting traditional sites of identity construction as well as bringing into tensions historicizing and idealizing visions of the natural environment to challenge the myths of Japanese‑Canadians’ identity that these sites were hitherto created to support. It brings into life a “Third Space” in the form of a personal island which will neither float to the Japanese Archipelago nor towards Canada, but it will be a separate entity including both. Hence, the dialogic relation between identity and rural and wilderness landscapes provides alternative forms of meaningful emplacement for the self — a personal “floating homeland” anchored in‑between the two cultures. Key words: Japanese‑Canadian, diasporic self, feeling of displacement, sense of belonging, Third Space, nature, landscape